Z-Monitor: A protocol analyzer for IEEE 802.15.4-based low-power wireless networks - Tennina, Stefano (2016)
Network sniffers are invaluable tools for designing, testing, commissioning and running distributed embedded systems. They become even more useful if these systems build on low-power wireless networks (LoWPAN), particularly when these scale in density and/or space and impose stringent quality-of-service requirements. This paper presents Z-Monitor, a low-cost and open-source network/protocol analyzer for LoWPANs. Z-Monitor is better than existing solutions since it combines the following features all-together: it covers the most widely used LoWPAN protocols, namely IEEE 802.15.4, 6LoWPAN, RPL and ZigBee; packet sniffing can be performed by any IEEE 802.15.4-compliant node, e.g., TelosB or MicaZ, requiring no extra hardware; the code is in Java (host PC), so it is OS-agnostic, and is freely available as open-source; Z-Monitor provides an user-friendly graphical user interface and a complete set of functionalities; nonetheless, Z-Monitor software architecture and programming approach are modular, so it is easily adaptable and extensible. We demonstrate and validate Z-Monitor in several LoWPAN network scenarios/settings and sites, ranging from a small-scale laboratory test-bed to a 400+ real-world deployment.